Colouring Textiles - Nieto-Galan, A. author. aut Link
XXVI, 246 p.
Keywords: Colouring Textiles is an attempt to provide a new cross-cultural comparative approach to the art of dyeing and printing with natural dyestuffs in the eighteenth and nineteenth centuries. Divided into thematic chapters, it uncovers new data from the vast historical heritage of natural dyestuffs from a range of European cities, to present new historiographic insights for the understanding of this technology. Through a sort of anatomic dissection, the book explores the study and cultivation of dye-plants in botanical gardens and plantations, and the tacit values hidden in dyeing workshops, factories, laboratories, or national and international exhibitions. It metaphorically submits the natural dyestuffs of the eighteenth and nineteenth centuries to a series of systematic historical tests, and traces back the circulation of those sources of colours through colonial spaces, dye works, cross-cultural networks, schools of artistic design, and science-based industries for the making of synthetic colorants. Colouring Textiles contributes to a better understanding of the role of natural dyestuffs in the processes of industrialization in Western Europe. Audience: Historians of science and technology, historians of chemistry, philosophers, economic historians, professional chemists, arts and crafts historians, and cultural anthropologists.